Bioactive Potential of Some Bacillus thuringiensis Strains from Macapá, Amazon, Brazil, Against the Housefly Musca domestica (Diptera: Muscidae) Under Laboratory Conditions - Tatiane Aparecida Nascimento; Maria José Paes; Fernando Hercos Valicente; Margareth Maria de Carvalho Queiroz (Insects)
The high pathogenic activity of Bacillus thuringiensis (Bt) strains against various insect orders has positioned it as the most effective, environmentally safe, and sustainable approach to integrated insect management. We aimed to identify Bt strains capable of effectively controlling the housefly Musca domestica, a species of significant medical, veterinary, and public health concern. Twelve Bt strains from Macapá, Brazil, were tested against housefly larvae. PCR was employed to detect genes encoding Cry and Cyt proteins and Vips. Six strains exhibited 70 to 100% larval mortality, with five containing cry genes, none harboring cyt genes, and four carrying vip genes. Scanning electron microscopy revealed the production of crystal inclusions with distinct morphologies: spherical (TR4J, SOL5DM, SOL6RN), cuboidal and bipyramidal (TRO1TN and TRO2MQ), and spherical and bipyramidal (UNI2MA). The potential presence of genes from the cry1, cry2, vip1, and vip3 families suggests that these strains also exhibit bioinsecticidal activity against other muscoid flies and insect pests across various orders. This study underscores the bioactive potential of these Brazilian Bt strains for developing new bioinsecticides.